Company's Views Concerning the Union - Beckman, Arnold O. (1946)
In a series of one page messages to the employees of National Technical Laboratories, Arnold Beckman laid out a case against unionization.
Keywords: United States. National Labor Relations Board; United Office and Professional Workers of America; Beckman Instruments, Inc.; Labor unions; Congress of Industrial Organizations (U.S.)